(untitled) (Journal of the College of Basic Education, 2023)
And prayers and peace be upon our master Muhammad, and upon his pure and immaculate family, and upon his noble companions.But after:The mind is considered the foundation, or the main pillar upon which the Mu’tazilites in general, and Judge Abd al-Jabbar al-Mu’tazili in particular, relies on, because of the clear importance of the mind in removing ambiguity from linguistic texts, interpreting the allegorical and referring it to the arbitrator, and knowing the evidences of justice and unification, truth and metaphor, as they are Subject to the mind and its significance, and I will try in this research to know the impact of the mind in those axes, and I ask God Almighty to make this research purely for the sake of the generous.The Mu’tazilites cared about the mind and their enemy’s basic cognitive evidence, and used it in controversy and discussion, and emphasized the precedence of the rational side over the auditory side, and its dominance. Judge Abd al-Jabbar al-Mu’tazili (d.The Mu’tazilites believe that with the mind it is possible to realize the ambiguity and ugliness of things, and to reach the aspect of clarity ().The Mu’tazilites, including Judge Abd al-Jabbar, balance between the rational evidence and the textual evidence, and they confirm that the two evidences are identical, and that access to them depends on the mental criterion.For this reason, the Mu’tazilah deliberately interpreted the verses that oppose the rational evidence, so the apparent meaning of these verses contradicts the mind, and the verses are decisive.